Development of multimedia learning courseware of grammar for children / Shamsuriayani Mohd Shakri - Mohd Shakri, Shamsuriayani (2014)
This project proposes a multimedia and learning courseware. Most people do not use correct grammar in their everyday casual speech and writing, even parents and teacher used incorrect grammar when speak with children. Currently there is no courseware in teaching solely on grammar available in Malaysia that used computerbased learning for children. Teachers did not try to use their creativity to make English an interesting and a fun subject for children. The objectives of the project are to design and develop E- - Grammar courseware for children and to evaluate the usability of the courseware. There are many elements needed to be considered in designing this courseware. That included the content of the courseware, screen design, functioning button and others. Thus, this courseware consists of animation, sound, and picture to encourage learning. The methodology used in this project is ADDIE method^It consists of five phases which are analysis (A), design (D), development (D), implementation (I), and evaluation (E). As a conclusion, this project had achieved its objectives even though some constraints occurred. The constraints are it is difficult in finding the best true to gather all the children for the evaluation. The finding of learning grammar is more effective compare to conventional method since the children improved their performance.